Shear Strength Model for Reinforced Concrete Corner Joints Based on Soft Computing Techniques - Moiz Tariq; Azam Khan; Asad Ullah; Muhammad Waseem; Hassan Nasir; Irfan Jamil (Advances in Civil Engineering)
The shear strength of cyclically loaded RC corner joints, resulting in opening and closing moments, has not been extensively studied. In addition, experimental studies of the joint shear strength are time-consuming and expensive. Therefore, to overcome this challenge, two separate gene expression programming (GEP) based empirical models are developed for the shear strength of the corner joints, one under the opening moment and the other under the closing moments. One of the key parameters overlooked in previous studies is the joint shear reinforcement, which has been incorporated in the GEP models. These models are developed by compiling an experimental database of 59 specimens in terms of the concrete compressive strength, the joint aspect ratio, the reinforcement tensile strength, and the reinforcement compressive strength. A detailed statistical study is undertaken that indicates superior accuracy of the proposed models and a high potential for their application in the design practice.